2016
DOI: 10.18632/oncotarget.12821
|View full text |Cite
|
Sign up to set email alerts
|

CDH4 suppresses the progression of salivary adenoid cystic carcinoma via E-cadherin co-expression

Abstract: The cadherin-4 gene (CDH4) of the cadherin family encodes non-epithelial R-cadherin (R-cad); however, the function of this gene in different types of cancer remains controversial. In this study, we found higher expression of CDH4 mRNA in a salivary adenoid cystic carcinoma (SACC) cell line with low metastatic potential (SACC-83) than in a cell line with high metastatic potential (SACC-LM). By analyzing 67 samples of SACC tissues and 40 samples of paraneoplastic normal tissues, we found R-cad highly expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
(34 reference statements)
0
16
0
Order By: Relevance
“…Similar to mucosal melanoma, the availability of reliable preclinical models is limited [ 51 ], and most published studies on expression and regulation of EMT-related proteins rely on retrospective studies with FFPE (Formalin-fixed paraffin-embedded) tissue samples. However, reduced expression of E-cadherin in salivary ACCs could be described as compared to paraneoplastic normal salivary tissue [ 52 ]. SNAI2 and E-cadherin expression were negatively associated in a cohort of 115 salivary ACC.…”
Section: Emt-like Phenotype In Salivary Gland Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to mucosal melanoma, the availability of reliable preclinical models is limited [ 51 ], and most published studies on expression and regulation of EMT-related proteins rely on retrospective studies with FFPE (Formalin-fixed paraffin-embedded) tissue samples. However, reduced expression of E-cadherin in salivary ACCs could be described as compared to paraneoplastic normal salivary tissue [ 52 ]. SNAI2 and E-cadherin expression were negatively associated in a cohort of 115 salivary ACC.…”
Section: Emt-like Phenotype In Salivary Gland Malignanciesmentioning
confidence: 99%
“…SNAI2 and E-cadherin expression were negatively associated in a cohort of 115 salivary ACC. High SNAI2 and low E-cadherin expression were significantly correlated with perineural invasion [ 52 ]. Yi et al investigated the expression of BMI1—a major component of the polycomb group complex 1 and a candidate stem cell marker—together with EMT-related proteins SNAI1, SNAI2, and E-cadherin in a cohort of 102 ACC patients [ 53 ].…”
Section: Emt-like Phenotype In Salivary Gland Malignanciesmentioning
confidence: 99%
“…Alaraudanjoki et al [34] Cadherin 4 (CDH4) rs2426986, rs16984837, and rs6101273 e encoded protein (R-cadherin) is a calcium-dependent cell-cell adhesion glycoprotein, which is highly expressed in oral mucosa and also linked to both Wnt and FGF signaling [39]. Recently, it has been shown that CDH4 also promotes the expression of E-cadherin [40], which plays a crucial role in enamel development [41].…”
Section: Ameloblastin (Ambn) Rs4694075mentioning
confidence: 99%
“…Moreover, Zhang et al (2000) noticed a correlation between E-cadherin expression and the degree of salivary ACC cell differentiation [28]. More recently, Xie et al (2016) recorded that cadherin 4 (CDH4) gene, responsible for retinal cadherin (R-cadherin) encoding, could inhibit the growth and metastasis of salivary ACC via co-expression with E-cadherin [29]. Zhao et al (2013) [30], similar to other authors [31,32], reported that reduced E-cadherin expression in salivary ACC correlated with solid type, advanced stages, perineural invasion, recurrences and distant metastasis.…”
Section: Figure 7 -(A) Statistical Analysis Proving a Strong Correlation Between E-cadherin And Vimentin Ihc Scores (R=0999 P=0027) (B) Amentioning
confidence: 99%